2021
DOI: 10.1149/1945-7111/ac2ec1
|View full text |Cite
|
Sign up to set email alerts
|

Forming Hard Anodic Films on Aluminum by Anodization in Oxalic Acid and Alcohol

Abstract: Porous anodic films have attracted wide attention because of their potential applications in various industrial fields. Reducing their porosity is expected to improve the hardness. This study focused on evaluating the effect of the electrolyte composition on the hardness of anodic alumina films formed on aluminum by anodization under mild conditions. In particular, the effect of adding alcohol (i.e., ethanol and ethylene glycol) to an oxalic acid–based electrolyte was considered. The voltage–time curve, coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
(60 reference statements)
0
15
1
Order By: Relevance
“…This result, together with the observed smaller porosity in the PAAs produced in the 1:3 v / v EtOH:H 2 O solution ( Figure 7 c), strongly suggests that the PAA formation efficiency increases at T > 10 °C in the etidronic electrolyte with the largest amount of ethanol. The higher efficiency of the oxide formation upon the addition of the alcohol was also found in the oxalic and sulfuric electrolytes [ 29 , 30 , 31 ]. As indicated in previous works (e.g., [ 12 , 27 ]), ethanol is a cooling agent that evaporates at the bottom of pores due to the high effumability taking away the heat generated at the reaction spot and preventing the increase of the localized temperature.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…This result, together with the observed smaller porosity in the PAAs produced in the 1:3 v / v EtOH:H 2 O solution ( Figure 7 c), strongly suggests that the PAA formation efficiency increases at T > 10 °C in the etidronic electrolyte with the largest amount of ethanol. The higher efficiency of the oxide formation upon the addition of the alcohol was also found in the oxalic and sulfuric electrolytes [ 29 , 30 , 31 ]. As indicated in previous works (e.g., [ 12 , 27 ]), ethanol is a cooling agent that evaporates at the bottom of pores due to the high effumability taking away the heat generated at the reaction spot and preventing the increase of the localized temperature.…”
Section: Resultsmentioning
confidence: 87%
“…Apart from the cooling effect, it was demonstrated that the addition of modifiers into an electrolyte can significantly change the process and influence the growth of PAA membranes [ 28 ]. The addition of ethanol was effective in suppressing the chemical dissolution of alumina into the electrolyte, thus improving the efficiency of the film formation (the ratio of the formed Al 2 O 3 to the consumed Al) under a constant charge [ 29 , 30 , 31 ]. Thanks to the lower dissociation power of the modified electrolyte, the maximal attainable PAA thickness was increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of the ethanol facilitates cooling of the electrolyte. 7,[62][63][64][65] The substrate was cooled via a Peltier stage until it was stable below <4 °C. Additional electrolyte cooling was provided via a custom-made ¼' stainlesssteel tube coil connected to an external cooler.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the specific anodization conditions, domains of close-packed pore arrays form, with diameters ranging from ∼20 nm -∼650 nm, lengths from ∼100 nm to >50 μm, with interpore spacings (D s ) from ∼50 nm to ∼500 nm, have been reported. [5][6][7][8][9][10][11][12][13] Initially led by Matsuda et al, AAO has attracted significant attention as a template for the fabrication of various nanostructured materials and devices. 14 These include, but are not limited to; sensors, [15][16][17][18][19] filters, [20][21][22][23] optics, [24][25][26][27][28][29] piezoelectrics, [30][31][32][33][34] catalysis, [35][36][37][38][39][40] and energy storage devices, [41][42][43][44][45][46] where it has played multiple roles.…”
mentioning
confidence: 99%